Facile fabrication of MoS2 nanocrystals confined in waste leather derived N, P co-doped carbon fiber for long-lifespan of sodium/potassium ion batteries. (January 2023) - Zheng, Jingao; Xiao, Fuyu; Jin, Hongjun; Cao, Changlin; Lei, Zewei; Wang, Yiyi; Wei, Mingdeng; Qian, Qingrong; Zeng, Lingxing; Chen, Qinghua
Abstract: Due to its slow kinetics and complicated multiphase development during cycling, developing anode materials for sodium/potassium-ion batteries (SIBs/PIBs) with high-rate and long-cycle simultaneously is still crucial and challenging. Additionally, the application of abundantly available, waste biomass to energy storage device has become a research hotspot. Herein, using waste leather as the adsorbent and bioreactor, we facilely fabricating the leather derived N/P co-doped carbon fiber composite with MoS2 nanocrystals after sulfuration treatment. Due to the intrinsic advantage of texture and component of collagen fiber, the ultrasmall MoS2 nanocrystals are evenly embedded with N/P co-doped carbon fibers. As expected, the MoS2 /NP-C anode shows enhanced sodium/potassium storage capacity. It exhibits a high specific capacity (368 mAh g −1 at 0.2 A g −1 ) for PIBs and amazing long-term cycling qualities (241 mAh g −1 at 1 A g −1 even after 2500 cycles) for SIBs. This work provides further insight into the application of waste biomass for fabricating nanocomposite in energy storage. Graphical abstract: By using waste leather as a reactive adsorbent and precursor, we fabricate the MoS2 /NP-C composite through a sulfidation treatment, which exhibits high-performance for the anode of sodium-ion and potassium-ion batteries. Image 1 Highlights: The waste leather and PMA were employed as nanoreactor and tanning agent, respectively. The MoS2 /NP-C shows reversible capacity of 241 mAh g −1 at 1 A g −1 after 2500 cycles. Leather derived N, P co-doped carbon fiber keeps the composite from collapsing.